Late Paleocene paleoclimate recorded in fluid inclusion of halite in Subei basin, East China - Ting Ding; Bing Pan; Hua Zhang; Chenglin Liu; Zhen Yang; M. Santosh (Scientific Reports, 2024)
Abstract Salt deposits are indicative of relatively extreme climate events. However, due to insufficient independent temperature proxies, paleotemperature records obtained from salt deposition are still lack. The Paleocene evaporite sequence deposited in the Hongze Depression of Subei Basin of eastern China provides an important terrestrial sediment record during this period. In this study we present total of 488 homogenization temperature (Th) data of halite fluid inclusions from drilling core with different stratigraphic depth after detailed petrological observation. The obtained Th ranged from 17.7 °C to 52.3 °C, with the mean Th value of 34.1 °C that in good agreement with the previous studies of climatic proxies. Our study shows that primary fluid inclusions of halite can serve as a robust tool to construct the ancient earth surface temperature.